2019
DOI: 10.1080/0020739x.2019.1603407
|View full text |Cite
|
Sign up to set email alerts
|

Specialist and more-able mathematics students: understanding their engagement with mathematics support

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…As such the centre described here is, importantly, not one which works primarily with non-specialist students at the transition into university which is the case often reported. While we do not discuss here the impact of the centre upon the students who choose to make use of it, its impact upon specialist mathematics students has recently been explored elsewhere (Grove et al 2019b). The findings from this work show that students value the centre because of the convenient availability of support, its personalised nature with friendly tutors of a similar-age and subject profile, and the opportunity to use the centre as a group study space to work with friends.…”
Section: Context Of the Studymentioning
confidence: 85%
See 2 more Smart Citations
“…As such the centre described here is, importantly, not one which works primarily with non-specialist students at the transition into university which is the case often reported. While we do not discuss here the impact of the centre upon the students who choose to make use of it, its impact upon specialist mathematics students has recently been explored elsewhere (Grove et al 2019b). The findings from this work show that students value the centre because of the convenient availability of support, its personalised nature with friendly tutors of a similar-age and subject profile, and the opportunity to use the centre as a group study space to work with friends.…”
Section: Context Of the Studymentioning
confidence: 85%
“…We have shown that tutors perceive their sharing of expertise has impacted upon their practices and consequently the evolution of the centre. It is known that the students on the receiving end of their support and, as a consequence, the University, benefit from their expertise and enthusiasm (Grove et al 2019b) and as such the tutors contribute to a thriving community of mathematics learners. Moreover, there are substantial benefits for the tutors themselves in terms of improved mathematical and pedagogical knowledge and skills, transferable skills of teamworking, communication and empathy, and a widening of their career aspirations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…were by mathematics students, and of all visits, almost two-thirds were made by mathematics students in either year 2 or beyond (Grove, Guiry & Croft, 2019b).…”
Section: A University-wide Mathematics Support Centre and Peer Assistmentioning
confidence: 99%
“…Within MLS, tutors work with some of the most vulnerable students, those lacking confidence, those with specific learning difficulties, and those most at risk of dropping out. Increasingly, MLS is also being accessed by the specialist and more-able student (Grove, Guiry and Croft, 2019;, one who is seeking to enhance and develop their mathematical skills and knowledge even further and occasionally beyond the boundaries of their module(s) of study. While many MLS tutors may have had some prior training as department tutors or lecturers, they are, as noted by Croft and Grove (2016, p.3), "in the front line of tackling the lack of confidence and skill deficits of students who arrive at support centres looking for help".…”
Section: Introductionmentioning
confidence: 99%